EXPLORING THE RELATIONSHIP BETWEEN TASKED-BASED LANGUAGE TEACHING AND FOSTERING CREATIVITY IN EFL EDUCATION - ZÚÑIGA, EULICES CORDOBA; MAYORGA, ESTEBAN; RUIZ, NANCY (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
This review article examines the role of task-based language teaching (TBLT) in promoting creativity in English as a foreign language (EFL) education. To do that, we collected, contrasted, and synthesized information from several sources, such as databases, school journals, Google Scholar, and other academic magazines, to ascertain the impact of TBLT on boosting creativity in the EFL training process. The results suggested that TBLT can be an effective pedagogical method for developing creativity among EFL students. The methodology enhances autonomy, imagination, and critical thinking and gives students time to generate new ideas on how to learn the language.